Electrolyte crystal dissolution-aiding additive, preparation method and use thereof

By using mixtures of organic acids, sodium organic acid salts, alcohols and amides in electrolyte crystal aid additives, the problem of long redissolution time of electrolyte solids added to water on the project site is solved, and the rapid dissolution and efficient industry of electrolyte solution is achieved .

CN114335644BActive Publication Date: 2025-02-25DALIAN RONGKE ENERGY STORAGE GRP CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202111588952.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-12-23
Publication Date
2025-02-25
Estimated Expiration
2041-12-23

AI Technical Summary

Technical Problem

The dissolution time of existing electrolyte solids during the water redissolution process on the project site is too long, resulting in high energy consumption and high cost.

Method used

An electrolyte crystal co-solvent additive, including a mixture of organic acids, sodium organic acid salts, alcohols and amides, is used to promote the redissolution of the crystal under water addition conditions.

Benefits of technology

The dissolution time of electrolyte crystals is significantly shortened, the dissolution energy consumption and time is reduced, the problem of long dissolution time in the prior art is solved, and the efficiency of industrial application of electrolytes is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003428507070000051
    Figure BDA0003428507070000051
  • Figure BDA0003428507070000052
    Figure BDA0003428507070000052
  • Figure BDA0003428507070000061
    Figure BDA0003428507070000061
Patent Text Reader

Abstract

The present invention provides an electrolyte crystal dissolution additive, a preparation method and use thereof, wherein the electrolyte crystal dissolution additive comprises a mixture of one or more of organic acids, organic acid sodium salts, alcohols and amides. The electrolyte crystal is an all-vanadium liquid flow battery electrolyte liquid crystal, and the all-vanadium liquid flow battery electrolyte liquid crystal is one or more of vanadium oxysulfate VOSO4, vanadium sulfate V2(SO4)3 crystals, VOCl2 crystals and VCl3 crystals. The present invention also discloses an electrolyte liquid crystal system, comprising the electrolyte crystal dissolution additive and the electrolyte liquid crystal, wherein the molar ratio of the all-vanadium crystal electrolyte dissolution additive to the electrolyte liquid crystal is 1:8 to 1:25. The additive of the present invention can significantly promote the redissolution of crystals under water conditions, which will solve the bottleneck problem for the use of crystal electrolytes.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to electrolyte technology, and in particular to an electrolyte crystal dissolution-promoting additive, a preparation method and use thereof. Background Art

[0002] As the energy storage medium for storing electrical energy in battery systems, electrolytes are often required for MW-level or even 10MW-level energy storage projects, exceeding thousands or even tens of thousands of cubic meters. This means that the transportation cost is huge when the energy storage project site is far away from the electrolyte production enterprise. How to use technical means to reduce the cost of this link is one of the research directions of future energy storage projects.

[0003] There are reports that different processes are used to obtain solid crystalline vanadium electrolytes from liquid electrolytes, which can greatly reduce transportation costs. However, the problem of long dissolution time when the crystals are dissolved in water again needs to be solved urgently. The focus of this project is on the re-dissolution technology of vanadium electrolyte liquid crystals at the energy storage project site, and its process breakthrough will greatly accelerate the industrialization of this project.

[0004] With the large-scale all-vanadium liquid flow batteries currently being widely put into operation, as additives in the electrolyte system, they must meet the following conditions: 1) the additives must be applicable to both positive and negative electrode solutions, 2) the additives must exist stably without affecting the battery system, or they must be oxidized or reduced during the battery charging and discharging process and decompose into water and CO2 and escape from the system.

[0005] The liquid flow battery electrolyte is processed into a solid electrolyte through a certain process, so that the volume of the electrolyte is greatly reduced by more than 60% compared with the electrolyte. For large-scale energy storage projects above MW level, the transportation cost will be reduced by more than 50%.

[0006] The problem with the existing process is that in the process of adding water to the above electrolyte solids to prepare the electrolyte at the project site, the dissolution time from solid to clarified liquid electrolyte often takes more than dozens of hours, which is a huge workload that is difficult to achieve at the project site, and often leads to high energy consumption and construction delays, and the actual cost has not been reduced. Summary of the invention

[0007] The purpose of the present invention is to propose an electrolyte crystal dissolution additive to address the current problem of long solid electrolyte dissolution time, resulting in high energy consumption and high cost. The additive can significantly promote the redissolution of crystals under water conditions, which will solve the bottleneck problem for the utilization of crystalline electrolytes.

[0008] To achieve the above object, the technical solution adopted by the present invention is: an electrolyte crystal dissolution additive, including a mixture of one or more of organic acids, organic acid sodium salts, alcohols and amides.

[0009] Furthermore, the electrolyte crystal is an all-vanadium liquid flow battery electrolyte liquid crystal, and the all-vanadium liquid flow battery electrolyte liquid crystal is a mixture of one or more of vanadium oxysulfate VOSO4, vanadium sulfate V2(SO4)3 crystals, VOCl2 crystals and VCl3 crystals.

[0010] Furthermore, the organic acid is benzoic acid and / or citric acid; the sodium salt of the organic acid is sodium benzoate and / or sodium citrate.

[0011] Furthermore, the alcohol is a primary alcohol with carbon number ≤ 3, preferably ethanol and / or propylene glycol.

[0012] Furthermore, the amides are urea and / or acetamide.

[0013] Furthermore, the electrolyte crystal dissolution aid additive includes citric acid, sodium citrate and propylene glycol, and the molar ratio of the three is 0.05-0.3:0.05-0.3:0.02-0.15, preferably 0.1:0.1:0.05.

[0014] Furthermore, the dissolution crystal dissolution additive includes citric acid, sodium citrate and urea, and the molar ratio of the three is 0.05-0.3:0.05-0.3:0.05-0.2, preferably 0.1:0.1:0.05.

[0015] Another object of the present invention is to disclose a method for preparing an electrolyte crystal dissolution-aiding additive, wherein various raw materials are mixed according to a proportion to obtain the electrolyte crystal dissolution-aiding additive.

[0016] Another object of the present invention is to disclose the use of an electrolyte crystal dissolution aid additive in the redissolution of a liquid flow battery electrolyte liquid crystal. The liquid flow battery electrolyte liquid crystal includes but is not limited to an all-vanadium liquid flow battery electrolyte liquid crystal. The all-vanadium liquid flow battery electrolyte liquid crystal is one or more of VOSO4, V2(SO4)3 crystal, VOCl2 crystal and VCl3 crystal.

[0017] Furthermore, at 5-40° C., an electrolyte crystal dissolution aid additive is added to an aqueous solution containing the all-vanadium liquid flow electrolyte liquid crystal to rapidly dissolve the all-vanadium liquid flow electrolyte liquid crystal, and the electrolyte is obtained by filtering.

[0018] Furthermore, the amount of the electrolyte crystal dissolution aid additive added is:

[0019] When the electrolyte crystal dissolution aid additive is citric acid and / or sodium citrate, the added concentration is 0.05 mol / L-0.5 mol / L electrolyte, preferably 0.05-0.3 mol / L electrolyte.

[0020] When the electrolyte crystal dissolution aid additive is ethanol or propylene glycol, the added concentration is 0.05 mol / L to 0.3 mol / L electrolyte, preferably 0.05 mol / L to 0.15 mol / L electrolyte.

[0021] When the electrolyte crystal dissolution aid additive is urea, its added concentration is 0.05 mol / L to 0.3 mol / L electrolyte, preferably 0.05 mol / L to 0.15 mol / L electrolyte.

[0022] When the electrolyte crystal dissolution additive is a mixture of citric acid, sodium citrate and propylene glycol, the total concentration of the electrolyte solution is 0.1-0.3 mol / L, wherein the concentration of each additive is controlled at 0.05 mol / L-0.15 mol / L;

[0023] When the electrolyte crystal dissolution additive is a mixture of citric acid, sodium citrate and urea, the total concentration of the electrolyte added is 0.1-0.3 mol / L, wherein the concentration of each additive is controlled at 0.05 mol / L-0.15 mol / L;

[0024] When the electrolyte crystal dissolution additive is a mixture of propylene glycol and urea, the total concentration of the additive added is 0.1-0.3 mol / L electrolyte, wherein the concentration of each additive is controlled at 0.05 mol / L-0.15 mol / L electrolyte;

[0025] When the electrolyte crystal dissolution aid additive is a mixture of citric acid, sodium citrate, propylene glycol and urea, the total concentration added is controlled at 0.1 mol / L to 0.3 mol / L electrolyte, preferably 0.1 mol / L to 0.25 mol / L electrolyte.

[0026] Furthermore, the effective filtration pore size of the filter bag is <10 μm, preferably <5 μm, so that the precipitable matter in the electrolyte can be removed through the filter bag.

[0027] Another object of the present invention is to disclose an electrolytic liquid crystal system, comprising an electrolyte crystal dissolution aid and an electrolytic liquid crystal, wherein the molar ratio of the all-vanadium crystal electrolyte dissolution aid and the electrolytic liquid crystal is 1:8 to 1:25, preferably 1:15 to 1:20. The electrolytic liquid crystal includes but is not limited to an all-vanadium liquid flow battery electrolytic liquid crystal. The all-vanadium liquid flow battery electrolytic liquid crystal is one or more of VOSO4, V2(SO4)3 crystal, VOCl2 crystal and VCl3 crystal.

[0028] Another object of the present invention is to disclose a method for preparing an electrolytic liquid crystal system, comprising the following steps:

[0029] Step 1, adding an electrolyte crystal dissolution aid to an electrolyte at 10-50° C. and stirring until all the electrolyte is dissolved; the electrolyte is an electrolyte whose main component is HCl and / or an electrolyte whose main component is H2SO4, wherein the concentration of HCl in the electrolyte whose main component is HCl is greater than 1.8 mol / L; the concentration of H2SO4 in the electrolyte whose main component is H2SO4 is greater than 0.5 mol / L;

[0030] Step 2: Stir the electrolyte in step 1 at low temperature (-5°C-10°C) to crystallize to obtain an electrolytic liquid crystal system.

[0031] When in use, deionized water and sulfuric acid are added, the temperature is raised to dissolve the electrolyte crystal system, and then filtered to obtain an electrolyte solution. The heating temperature is 25 to 35° C., preferably 30° C. Sulfuric acid is added when in use because insufficient H2SO4 is added when making electrolyte crystals, so that the electrolyte solution is easier to crystallize.

[0032] Another object of the present invention is to disclose a method for preparing an electrolytic liquid crystal system, comprising the following steps:

[0033] Step 1, stirring the electrolyte at low temperature (-5°C-10°C) to crystallize to obtain an electrolyte liquid crystal; the electrolyte is an electrolyte whose main component is HCl and / or an electrolyte whose main component is H2SO4, the concentration of HCl in the electrolyte whose main component is HCl is greater than 1.8 mol / L; the concentration of H2SO4 in the electrolyte whose main component is H2SO4 is greater than 0.5 mol / L

[0034] Step 2: Mix the electrolytic liquid crystal with the electrolyte crystal dissolution aid to obtain an electrolytic liquid crystal system.

[0035] When used, deionized water and sulfuric acid are added, the temperature is raised to dissolve the electrolyte crystals, and the electrolyte is filtered to obtain an electrolyte solution. The temperature is raised to 25 to 35°C, preferably 30°C.

[0036] The electrolyte crystal dissolution-promoting additive of the present invention is a dissolution-promoting additive used in the key technology of liquid flow battery - the redissolution of liquid flow battery electrolyte liquid crystals. Compared with the prior art, it has the following advantages:

[0037] 1) The electrolyte crystal dissolution additive of the present invention is suitable for the complex dissolution promoter of VOSO4 and V2(SO4)3 or VOCl2 and VCl3 crystals. The dissolution additive greatly shortens the dissolution time of the electrolyte crystals, greatly reducing the economic costs such as dissolution energy consumption and time.

[0038] 2) The co-solvent of the present invention is an organic small molecule. After the crystals are redissolved, they will be oxidized and decomposed into CO2, H2O, N2, etc. and discharged from the system during battery operation, which has no effect on system performance

[0039] In summary, based on the liquid flow battery electrolyte liquid crystal processing technology, the present invention has found through practical summary that the additive of the present invention can significantly promote the redissolution of crystals under water conditions, which will solve the bottleneck problem for the utilization of crystal electrolytes. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 The energy efficiency comparison between the electrolyte containing 0.15 mol / L citric acid as a solubilizing additive in Example 1 and the control electrolyte;

[0041] Figure 2 The current efficiency comparison of the electrolyte containing the solubilizing additives 0.10 mol / L citric acid and 0.05 mol / L acetamide in Example 2;

[0042] Figure 3 The energy attenuation comparison of the electrolyte containing the dissolution-aiding additives 0.1 mol / L citric acid, 0.1 mol / L urea and 0.05 mol / L propylene glycol in Example 3;

[0043] Figure 4 The energy efficiency comparison of the HCl electrolyte containing the solubilizing additives 0.15 mol / L sodium citrate and 0.07 mol / L propylene glycol in Example 4;

[0044] Figure 5 The voltage energy efficiency comparison of the electrolyte containing the solubilizing additive 0.1 mol / L acetamide + 0.1 mol / L propylene glycol in Example 5 is shown. DETAILED DESCRIPTION

[0045] The present invention is further described below in conjunction with embodiments:

[0046] Example 1

[0047] Sulfuric acid electrolyte, Vn+: 1.7 mol / L, 50% each of trivalent V and tetravalent V ions, SO4 2- :3.5mol / L, cool down (5℃) and stir 2L of each, one of which is used as the control electrolyte, and add citric acid to the other solution to make the total content 0.15mol / L. After waiting for the solution to crystallize, filter the crystals and store them separately.

[0048] Table 1 Redissolution comparison

[0049]

[0050] Comparison of energy efficiency between electrolyte containing 0.15 mol / L citric acid as solubilizing additive and control electrolyte Figure 1 As shown,

[0051] Where CE: current efficiency; EE: energy efficiency; VE: voltage efficiency;

[0052] Depend on Figure 1 The data shows that after adding 0.15 mol / L citric acid as a dissolution aid additive to the vanadium sulfate electrolyte, the efficiency of the electrolyte remained stable during operation after the crystals were repeatedly dissolved, and was slightly higher than that of the control electrolyte battery. This shows that while the dissolution aid increases the dissolution rate, it has no effect on the battery performance.

[0053] Example 2

[0054] Sulfuric acid electrolyte, Vn+: 2.0 mol / L, 50% each of trivalent V and tetravalent V ions, SO4 2- :3.5mol / L, cool down (10℃) and stir 20L of each, one of which is used as the control electrolyte, and add citric acid and acetamide to the other solution. After the solution crystallizes, filter the crystals and store them separately.

[0055] Table 2 Redissolution comparison

[0056]

[0057] Comparison of current efficiency of electrolytes containing solubilizing additives 0.10 mol / L citric acid and 0.05 mol / L acetamide Figure 2 shown.

[0058] Depend on Figure 2 The data shows that after adding 0.10 mol / L citric acid and 0.05 mol / L acetamide as dissolution additives to the vanadium sulfate electrolyte, the current efficiency of the electrolyte remained stable during operation after repeated dissolution of the crystals, and was slightly higher than that of the control electrolyte battery. This indicates that while the dissolution aid increases the dissolution rate, it has no effect on the battery performance.

[0059] Example 3

[0060] Sulfuric acid and hydrochloric acid mixed electrolyte, Vn+: 3.0mol / L, 50% each of trivalent V and tetravalent V ions, SO4 2- :1.5mol / L,Cl - :8.0mol / L. Cool down (5℃) and stir 50L of each solution. One portion is used as the control electrolyte. Add citric acid, urea and propylene glycol to the other solution. After the solution crystallizes, filter the crystals and store them separately.

[0061] Table 3 Redissolution comparison

[0062]

[0063] Comparison of energy decay of electrolytes containing solubilizing additives 0.1 mol / L citric acid, 0.1 mol / L urea and 0.05 mol / L propylene glycol Figure 3 shown.

[0064] Depend on Figure 3 The data shows that after adding 0.1 mol / L citric acid, 0.1 mol / L urea and 0.05 mol / L propylene glycol as dissolution additives to the vanadium sulfate electrolyte, the battery energy decay rate of the electrolyte during operation was good after repeated dissolution of the crystals, and was better than that of the control electrolyte battery. This shows that while the dissolution agent increases the dissolution rate, it has no effect on the battery performance.

[0065] Example 4

[0066] Hydrochloric acid electrolyte, Vn+: 2.4 mol / L, 50% each of trivalent V and tetravalent V ions, Cl - :8.5mol / L. Cool down (5℃) and stir 50L of each solution. One portion is used as the control electrolyte. Sodium citrate and propylene glycol are added to the other solution. After the solution crystallizes, filter the crystals and store them separately.

[0067] Table 4 Redissolution comparison

[0068]

[0069]

[0070] Comparison of energy efficiency of HCl electrolyte containing solubilizing additives 0.15 mol / L sodium citrate and 0.07 mol / L propylene glycol Figure 4 shown.

[0071] Depend on Figure 4 The data shows that after adding 0.15 mol / L sodium citrate and 0.07 mol / L propylene glycol as dissolution additives to the vanadium hydrochloride electrolyte, the battery energy efficiency of the electrolyte was good during operation after repeated dissolution of the crystals, and was better than that of the control electrolyte battery. This shows that while the dissolution agent increases the dissolution rate, it has no effect on the battery performance.

[0072] Example 5

[0073] Sulfuric acid electrolyte, Vn+: 1.7 mol / L, 50% each of trivalent V and tetravalent V ions, SO4 2- :4.2mol / L. Cool down (5℃) and stir 50L of each solution. One portion is used as the control electrolyte. Add acetamide and propylene glycol to the other portion to a concentration of 0.1mol / L each, and a total content of 0.2mol / L. After the solution crystallizes, filter the crystals and store them separately.

[0074] Table 5 Redissolution comparison

[0075]

[0076] Comparison of energy efficiency of electrolyte containing solubilizing additives 0.1mol / L acetamide + 0.1mol / L propylene glycol Figure 5 shown.

[0077] Depend on Figure 5 The data shows that after adding 0.1 mol / L acetamide + 0.1 mol / L propylene glycol as dissolution additives to the vanadium sulfate electrolyte, the battery voltage energy efficiency of the electrolyte during operation is good after repeated dissolution of the crystals, and is better than that of the control electrolyte battery. This indicates that while the dissolution aid increases the dissolution rate, it has no effect on the battery performance.

[0078] Example 6

[0079] Sulfuric acid, hydrochloric acid mixed electrolyte, V n+ :2.2mol / L, 50% each of trivalent V and tetravalent V ions, Cl - :4.0mol / L, SO4 2- :4.0mol / L. Cool down (5℃) and stir 50L of each solution. One portion is used as the control electrolyte. Add citric acid and propylene glycol to the other portion to a concentration of 0.08mol / L each, and a total content of 0.16mol / L. After the solution crystallizes, filter the crystals and store them separately.

[0080] Table 6 Redissolution comparison

[0081]

[0082] Depend on Figure 4 The data show that after adding 0.08 mol / L sodium citrate and 0.08 mol / L propylene glycol as dissolution additives to sulfuric acid and vanadium hydrochloride electrolytes, the repeated dissolution rate of the crystals is significantly better than that of the control electrolyte without additives.

[0083] Example 7

[0084] Sulfuric acid, hydrochloric acid mixed electrolyte, V n+ :2.2mol / L, 50% each of trivalent V and tetravalent V ions, Cl - :3.0mol / L, SO4 2- :4.0mol / L. Cool down (5℃) and stir 50L of each solution. One portion is used as the control electrolyte. Add citric acid to a concentration of 0.1mol / L and urea to a concentration of 0.05mol / L to the other portion of the solution, until the total content is 0.15mol / L. After the solution crystallizes, filter the crystals and store them separately.

[0085] Table 7 Redissolution Comparison

[0086]

[0087] Depend on Figure 4 The data show that after adding 0.1 mol / L sodium citrate and 0.05 mol / L urea as dissolution additives to sulfuric acid and vanadium hydrochloride electrolytes, the repeated dissolution rate of the crystals is significantly better than that of the control electrolyte without additives.

[0088] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. Use of an electrolyte crystal dissolution additive in the redissolution of an electrolyte liquid crystal in an all-vanadium redox flow battery, characterized in that: The electrolytic liquid crystal system comprises an electrolyte crystal dissolution aid and an electrolytic liquid crystal, wherein the molar ratio of the electrolyte crystal dissolution aid to the electrolytic liquid crystal is 1:8 to 1:25; The preparation method of the electrolytic liquid crystal system comprises the following steps: Step 1, adding an electrolyte crystal dissolution aid to an electrolyte at 10-50° C. and stirring until all the electrolyte is dissolved; the electrolyte is an electrolyte whose main component is HCl and / or an electrolyte whose main component is H2SO4; Step 2, stirring the electrolyte in step 1 at low temperature to crystallize to obtain an electrolytic liquid crystal system; the low temperature is -5°C-10°C; When in use, deionized water and sulfuric acid are added, the temperature is raised to dissolve the electrolytic liquid crystal system, and then filtered to obtain an electrolyte solution; The electrolyte crystal dissolution aid additive is composed of two or more of organic acids, organic acid sodium salts, alcohols and amides; The electrolyte crystal is an all-vanadium liquid flow battery electrolyte liquid crystal, which is a mixture of vanadyl sulfate VOSO4, vanadium sulfate V2(SO4)3 crystals, VOCl2 crystals and VCl3 crystals; the all-vanadium liquid flow battery electrolyte liquid crystal contains trivalent V and tetravalent V; The organic acid is benzoic acid and / or citric acid; the sodium salt of the organic acid is sodium benzoate and / or sodium citrate; the alcohol is a primary alcohol with carbon number ≤ 3; and the amide is urea and / or acetamide.

2. The use of the electrolyte crystal dissolution-promoting additive according to claim 1 in the redissolution of the electrolyte liquid crystal of the all-vanadium redox flow battery, characterized in that: The electrolyte crystal dissolution aid additive comprises citric acid, sodium citrate and propylene glycol, and the molar ratio of the three is 0.05-0.3:0.05-0.3:0.02-0.

15.

3. The use of the electrolyte crystal dissolution-promoting additive according to claim 1 in the redissolution of the electrolyte liquid crystal of the all-vanadium redox flow battery, characterized in that: The dissolution crystal dissolution additive comprises citric acid, sodium citrate and urea, and the molar ratio of the three is 0.05-0.3:0.05-0.3:0.05-0.2.

Citation Information

Patent Citations

  • Method for preparing all vanadium ion redox flow battery electrolyte

    CN101110481A

  • Method for preparing all-vanadium ion redox flow battery electrolyte

    CN102376970A